2009
DOI: 10.3354/meps07846
|View full text |Cite
|
Sign up to set email alerts
|

Diverse foraging strategies in lactating New Zealand sea lions

Abstract: Diving and foraging behaviours of marine predators are thought to be coupled with species demographics, with benthic foraging species found to have small population sizes and low growth rates. This was thought to be the case for New Zealand (NZ) sea lions Phocarctos hookeri, previously identified as solely benthic foragers with a small declining population. Female NZ sea lions dive deeper and for longer than any other otariids (eared seals). They exceed their calculated aerobic dive limits (cADL) during 68% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(83 citation statements)
references
References 40 publications
5
78
0
Order By: Relevance
“…This may not hold true for sea lions because hake and market squid have a relatively low energy content compared with prey that is likely targeted by females using Strategies 1 and 3, such as schooling and mesopelagic fishes (Huynh and Kitts 2009;Litz et al 2010). A similar pattern, that high cost does not equal high reward, has also been suggested for foraging strategies of New Zealand sea lions (Chilvers and Wilkinson 2009) and northern fur seals (Callorhinus ursinus; Costa and Gentry 1986). Energetic data in support of these hypotheses are lacking for California sea lions, yet should be a focus of future research because of the influence of maternal energy balance on pup growth and survival.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This may not hold true for sea lions because hake and market squid have a relatively low energy content compared with prey that is likely targeted by females using Strategies 1 and 3, such as schooling and mesopelagic fishes (Huynh and Kitts 2009;Litz et al 2010). A similar pattern, that high cost does not equal high reward, has also been suggested for foraging strategies of New Zealand sea lions (Chilvers and Wilkinson 2009) and northern fur seals (Callorhinus ursinus; Costa and Gentry 1986). Energetic data in support of these hypotheses are lacking for California sea lions, yet should be a focus of future research because of the influence of maternal energy balance on pup growth and survival.…”
Section: Discussionmentioning
confidence: 77%
“…Given that sea lions were only tracked across a 2-month period, we cannot make conclusions about whether these individual behavioral patterns may persist across longer temporal scales. Studies of other otariids have found that fidelity to a single foraging strategy is often retained across multiple years (Chilvers and Wilkinson 2009;Kernaléguen et al 2012;Baylis et al 2015;Kernaléguen et al 2016); however, many of these studies have focused on populations that inhabit less variable environments than the CCS. Villegas-Amtmann et al (2011) found that adult female California sea lions from the Gulf of Mexico exhibited three foraging strategies during the warm, unproductive season, but only one during the cold season, indicating that the degree of intraspecific variability in behavior may be driven by Dive rate (dives h −1 ) 19.6 ± 6.8 24.7 ± 5.6 NA 13.2 ± 2.8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) have the longest and deepest dives of all otariids (Gales & Mattlin 1997;Costa & Gales 2000;Chilvers et al 2006) and travel some of the greatest distance during a foraging trip (Chilvers et al 2005). Enderby Island female New Zealand sea lions have two distinct dive profile types or foraging patterns (foraging specialisation): a benthic diving profile; and a deeper, more varied mesopelagic diving profile; with individual females showing only one foraging type across seasons and years (Chilvers et al 2006;Chilvers & Wilkinson 2009). Both of these foraging strategies result in females exceeding their calculated aerobic dive limits (cADL) on average during 68% of all dives, and this finding, coupled with the extensive distances travelled, indicates that they are operating at or near their maximum physiological capacity (Chilvers et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this research was to identify where lactating females from these two breeding locations forage and determine whether they utilize separate foraging areas and the extent of these areas' overlap with fisheries activities. The foraging areas of 26 females from Enderby Island have been previously investigated Chilvers and Wilkinson 2009). Female NZ sea lions from Enderby Island show extreme site fidelity to foraging locations both within and between years (Chilvers 2008b).…”
Section: Introductionmentioning
confidence: 99%